Steroid Transformations by Species of Cephalosporium and Other Fungi - Sardinas, Joseph L. (1967)
A total of 58 cultures, tentatively identified as species of the genus Cephalosporium, were screened in flask fermentations for their ability to effect conversions of progesterone (Δ(4)-pregnene-3,20-dione) and Reichstein's Substance S (Δ(4)-pregnene-17α,21-diol-3,20-dione). A large number of transformations were observed by means of a series of five paper chromatography systems rated for analysis of steroid compounds ranging in polarity from progesterone to polyhydroxylated steroids. Five different transformation products were selected for isolation and identification. For purposes of recovery, conversions were conducted under submerged conditions in either 4- or 200-liter fermentors in which the broth was agitated and aerated. The steroid substrate was dissolved in acetone and added aseptically to the growing culture in a final concentration of 0.025%. After the conversions were effected, the whole broth was extracted with chloroform, and the transformation products were recovered, either by direct crystallization from solvents or through the use of silica gel columns. It was determined that C. ciferrii 21C converted progesterone to Δ(4)-androstene-3,17-dione. Kendall's Compound F (Δ(4)-pregnene-11β,17α,21-triol-3,20-dione) was converted to its 20β-ol analogue by Geotrichum sp. 51C (during these studies, a number of cultures were taxonomically reclassified). Cephalosporium sp. 27C formed the Δ(1)-analogue of Reichstein's Substance S, and Cephalosporium sclerotigenum 31C and Verticillium aphidum both converted Substance S to the 6β-hydroxy derivative. Paecilomyces persicinus 22C converted Substance S to a product believed to be a dihydroxylated derivative.